Quality – Key factor for high value in professional patent, technical and scientific information - Brünger-Weilandt, Sabine; Geiß, Dieter; Herlan, Gerhard; Stuike-Prill, Rainer (World patent information, 2011)
An effective and efficient innovation process needs reliable scientific, technical and patent information of high quality. To obtain information of high quality, specific quality criteria during the entire information workflow have to be followed. This article focuses on quality criteria for database producers, information providers and information specialists. In particular, STN International ® is used as an example to describe in detail the quality criteria for information providers, and the value they add through a comprehensive information offer. This includes value-add patent databases; quality assurance of databases; a standardized host environment; a transparent and sophisticated retrieval system; ensured data security and privacy; and professional and qualified customer support. ► Quality in patent, technical and scientific information searching – the information providers’ perspective. ► Quality criteria and value-add are key aspects. ► More specifically – quality assurance of databases, a standardized host environment, a transparent and sophisticated retrieval system, data security and privacy, and expert customer support are explored. ► The continuous nature and significance of quality criteria in relation to customer demands is emphasized.